Youth and employment among the BRICS - Michael MacLennan; Rafael Guerreiro Osório; Pedro Lara de Arruda (International Policy Centre for Inclusive Growth (IPC-IG), 2014)
"Come and Hope with Me!" This was the rallying call by South African Mongane Serote to draw the world's attention to the battle fought by his people against Apartheid. It is in this spirit that we invite readers to explore this special edition of Policy in Focus. This issue is dedicated to the analysis of the usage of social programmes to promote youth employment in the BRICS (Brazil, Russia, India, China and South Africa) countries. In light of the 2014 BRICS Academic Forum, which will officially transfer the responsibilities of host country from South Africa to Brazil, we have set out to understand how the BRICS countries have made use of their extensive expertise in social policies and programmes to go beyond mitigation of crisis, towards the realisation of young people's ambitions. [...]
Keywords: 330